A novel functional water significantly modulates the gut microbiota and decreases the basal level of inflammation in mice - Men, Yinghui; Yue, Lixia; Zhang, Mingchao; Wang, Bing; Ying, Weihai (Frontiers in Nutrition, 2026)
BackgroundAccumulating evidence has identified the gut microbiota as a critical regulator of biological processes such as immune homeostasis, and its dysbiosis has been implicated in the pathogenesis of numerous diseases. Current strategies for modulating the gut microbiota remain limited by several challenges: low colonization efficiency (probiotics), interindividual variability in host response (prebiotics), and safety concerns (antibiotics).MethodsWe investigated the effects of a physically processed, additive-free purified water (Koishio water, KW) on gut microbiota composition and basal inflammatory status in healthy mice.ResultsFirst, KW drinking significantly increased the diversity and richness of the gut microbiota of the mice, including increased abundance of Verrocomicrobiota and decreased abundance of Proteobacteria; Second, KW drinking significantly increased the abundance of several beneficial genera of the gut bacterium (Akkermansia, Faecalibaculum, Ligilactobacillus, and Muribaculum) and significantly decreased the abundance of several harmful genera of the gut bacterium (Clostridioides, Citrobacter, Escherichia-Shigella, and Clostridium Innocuum group); and third, functional prediction suggested enrichment of microbial pathways related to mucosal barrier integrity, host metabolic regulation, and antioxidative capacity. Moreover, KW significantly decreased the basal level of three major pro-inflammatory factors, including IL-1β, IL-6, and TNF-α, which are widely recognized as biomarkers of subclinical low-grade chronic inflammation.ConclusionThese findings demonstrate that KW, characterized by affordability, safety, and suitability for daily consumption, may serve as a novel non-pharmacological intervention to beneficially modulate gut microbiota composition and reduce basal inflammatory levels under non-pathological conditions.